2017
DOI: 10.1016/j.neurobiolaging.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and interaction studies of CSF T-tau/Aβ42 ratio in ADNI cohort

Abstract: The pathogenic relevance in Alzheimer’s disease (AD) presents a decrease of cerebrospinal fluid (CSF) amyloid-β42 (Aβ42) burden and an increase in CSF total-tau (T-tau) levels. In this work, we performed genome-wide association study (GWAS) and genome-wide interaction study (GWIS) of T-tau/Aβ42 ratio as an AD imaging quantitative trait (QT) on 843 subjects and 563,980 single nucleotide polymorphisms (SNPs) in ADNI cohort. We aim to identify not only SNPs with significant main effects but also SNPs with interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In this respect, AD presents a decrease of CSF amyloid-ß 42 (Aß 42 ) burden and an increase in cerebrospinal fluid total tau (T-tau). Genome-wide association study (GWAS) and interaction study of T-tau/Aß 42 robustly replicated previously reported AD-related genes APOE4, APOC1, and TOMM40 and suggested other influencing factors, warranting future investigation [11]. Focusing on phosphorylated tau, GWAS identified a panel of five SNPs, rs6766238, rs1143960, rs1249963, rs11975968, and rs4836493, that are predictive for p-tau181/Aβ1-42 ratio (high/low), suggesting a panel of SNPs as a potential prognostic biomarker in ApoE4-negative MCI patients [12].…”
supporting
confidence: 66%
“…In this respect, AD presents a decrease of CSF amyloid-ß 42 (Aß 42 ) burden and an increase in cerebrospinal fluid total tau (T-tau). Genome-wide association study (GWAS) and interaction study of T-tau/Aß 42 robustly replicated previously reported AD-related genes APOE4, APOC1, and TOMM40 and suggested other influencing factors, warranting future investigation [11]. Focusing on phosphorylated tau, GWAS identified a panel of five SNPs, rs6766238, rs1143960, rs1249963, rs11975968, and rs4836493, that are predictive for p-tau181/Aβ1-42 ratio (high/low), suggesting a panel of SNPs as a potential prognostic biomarker in ApoE4-negative MCI patients [12].…”
supporting
confidence: 66%
“…Table 1 shows the SNPs with FDR < 0.05 from the QTL analysis of Aβ 42 , T-tau/Aβ 42 ratio, p-tau/Aβ 42 ratio and ADAS13, respectively. A total of five SNPs were identified according to the threshold FDR < 0.05, and they were also reported by previous studies ( Li et al, 2017 ). Detected SNPs rs2075650, rs157580 and rs157582 are located within gene TOMM40.…”
Section: Resultsmentioning
confidence: 99%
“…This promotes studies on very large cohorts e.g. (Adhikari et al, 2018), the development of reference databases (see for Alzheimer disease (Li et al, 2017), Parkinson disease (Chahine et al, 2018) or Human connectome project (Hodge et al, 2016)) and fair and robust comparison of image processing solutions (Commowick et al, 2018). Here, we propose to use the extension of the SHANOIR environment (Barillot et al, 2016) for storing preclinical imaging data, coupled with the VIP architecture for the dedicated image processing pipelines execution (Glatard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%